Does the EU’s Paediatric Regulation work for new medicines for children in Denmark, Finland, Norway and Sweden? A cross-sectional study - Elin Kimland; Ann Marie Tötterman; Siri Wang; Pirkko Lepola; Ninna Gullberg; Kirstine Moll Harboe (BMJ Paediatrics Open)
Objective The aim of this study was to assess the marketing status of the new paediatric medicinal products listed in the 10-year report as initially authorised between 2007 and 2016, reflecting the product availability in four Nordic countries.Design This is a cross-sectional study.Setting Analysis of the national medicine agency’s databases in Denmark, Finland, Norway and Sweden.Data source New medicinal products with paediatric indications and new paediatric formulations listed in the Annex of European Medicines Agency’s EU Paediatric Regulation 10-year report.Data analysis The products were classified according to national marketing status between January 2019 and March 2019, whether a product was authorised and whether the product was marketed.Main outcome measures The percentages of the new medicinal products with paediatric indications and new paediatric formulations having a valid marketing authorisation and being marketed, both in terms of the sums of all countries and separately for each country.Results Across the four countries, 21%–32% (16/76–24/76) of the new medicinal products were not marketed. Of the new formulations relevant to children, 29%–50% (16/56–28/56) were not marketed, and a significant proportion of these products had never been marketed.Conclusions This study reflects the reality of the implementation of the Paediatric Regulation. The results show that several new paediatric medicines and new formulations are not marketed. This affects the product availability. Similar data from other countries are needed to evaluate the overall European status to find remedies to current situation and increase the availability of the medicines for children.